PENGARUH PENDIDIKAN, PELATIHAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU SMP NEGERI 1 PENAJAM PASER UTARA - jurnalmap map; Daniel ÔÇì; Indra Prasetyo; ÔÇì Chamariyah ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
ABSTRACT This research is to study education and training, teaching experience partially or simultaneously on the professionalism of teachers in the State Junior High School 1 Penajam Paser Utara, East Kalimantan. The study used a survey with a total population of 35 people. The results of the study are simultaneous education and training and teaching experience about the professionalism of teacher teachers in Penajam Paser Utara 1 Public Middle School. Professional teacher education and teaching in Penajam Paser Utara 1 Public Middle School; and teacher experience including an understanding of the professionalism of teachers in Penajam Paser Utara 1 Public Middle School. Keywords: education and training, teaching experience, teacher professionalism